Modern Farming Biofloc ponds for tilapia aquaculture based on the internet of things use a fuzzy logic algorithm - Mabe Parenreng, Jumadi; Syahrul, Syahrul; Wahid, Abdul; Sary, Desta Winda (Internet of Things and Artificial Intelligence Journal, 2022)
This study aims to create a smart system in controlling tilapia biofloc ponds. The type of research is laboratory experiments and the category of system testing, namely Functionality testing, is used to measure the performance of the system hardware. Testing the functionality of the prototype is tested in 2 stages, the first test begins with knowing the accuracy of sensor data and testing manually. The second test is to test the prototype as a whole, namely by giving treatment so that the performance of the prototype can be known as desired. The results obtained when the temperature is cold, the water heater heater will turn on and treatment to the pH sensor is obtained, namely an acidic pH condition, then the water pump will turn on and drain the water until the ultrasonic sensor detects the maximum water level that can be drained. Testing on feeding is by monitoring the servo successfully rotating, opening and closing the feed storage container based on the time that has been set. The results of monitoring feeding in the morning, afternoon and evening are successful and can send notifications. Based on the test results, the resulting " Modern Farming Biofloc ponds for tilapia aquaculture based on the internet of things use a fuzzy logic algorithm" can run as expected.